Effective utilisation of waste cooking oil in a single-cylinder diesel engine using alumina nanoparticles. Issue 2 (25th November 2019) - Roy, Sumit; Parsi, Pranay Kumar; Kotha, R. Sreeram; Barman, Sanmitra; Vinayak, Kalluri; Roy, Mili Mitra; Banerjee, Rahul
Abstract : First-of-a-kind endeavour exploiting the effects of nanoparticles on the performance and emission spectra of biodiesel derived from waste cooking oil. Abstract : Considering the rapid decline in the amount of fossil fuels and the large quantities of emissions they release into the atmosphere, which are responsible for global warming, researchers are looking for alternative sources of energy. Biodiesel is an alternative source that is suitable for use as an alternative to diesel and can result in a reduction in the level of pollutants released. It has been observed that trans-esterified cooking oil can be combusted in an internal combustion engine like different biofuels with no major adjustments. Recent studies have proved that with the addition of nanoadditives, the performance and emissions have a very good impact on the environment. In the present experimental study, trans-esterified vegetable oil was used as biodiesel, along with the addition of nanoadditives (alumina) to diesel, and the outcomes were compared with baseline diesel operation. The nanoadditive was blended in the fuel mixture alongside an appropriate surfactant. Various blends were made and used for this investigation. Performance, emission and combustion parameters were studied using a single-cylinder four-stroke diesel engine at various loads, keeping a constant compression ratio of 18. Due to the availability of oxygen in the biodiesel and the better blending capacities of the nanoparticles, it was observed that there was a reduction in the opacity, CO and HC emissions; however, there was a small increment in NOx. It was also observed that the specific fuel consumption decreased with the increase in in-cylinder pressures. The outcomes showed that the addition of alumina in the diesel-biodiesel mixture has a positive overall effect on the environment.